Meet Felicity an American Girl Book One - Ripp, Valerie (Pleasant Company Publications, 1951)
Felicity saves a mistreated horse, decides about the tea boycott, nurses her mother back to health, discovers a gunpowder plot, helps her friend, and faces the start of the revolution.
Keywords: Juvenile literature-Fiction